2004
DOI: 10.31899/rh2.1002
|View full text |Cite
|
Sign up to set email alerts
|

The Tostan program: Evaluation of a community based education program in Senegal

Abstract: This operations research project evaluated the effect and impact of a basic education program, developed by TOSTAN, a non-governmental organization based at Thiès, Senegal. The basic education program consists of four modules: hygiene, problem solving, women's health, and human rights. Through these four themes, emphasis was placed on enabling the participants, who were mostly women, to analyze their own situation more effectively and thus find the best solutions for themselves. The Supra Regional Project for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 0 publications
0
70
0
Order By: Relevance
“…In these patriarchal settings in which FGM/C is strongly linked to tradition and religion and in which the target audience received education on hygiene, problem-solving, human rights and women’s health that might not have addressed their needs and wants, little change in FGM/C-related beliefs and behaviour ensued. Rather, women failed to participate because ‘their husbands forbade it’26 and male villagers expressed hostility for not being included from the start and, once included, dominated in committees. Some beneficiaries believed ‘the programme was coming to fight against the traditional culture.’26 None of the included texts suggested that religion was addressed in the Tostan programme, although it was a chief factor in its continuance in all communities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these patriarchal settings in which FGM/C is strongly linked to tradition and religion and in which the target audience received education on hygiene, problem-solving, human rights and women’s health that might not have addressed their needs and wants, little change in FGM/C-related beliefs and behaviour ensued. Rather, women failed to participate because ‘their husbands forbade it’26 and male villagers expressed hostility for not being included from the start and, once included, dominated in committees. Some beneficiaries believed ‘the programme was coming to fight against the traditional culture.’26 None of the included texts suggested that religion was addressed in the Tostan programme, although it was a chief factor in its continuance in all communities.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, women failed to participate because ‘their husbands forbade it’26 and male villagers expressed hostility for not being included from the start and, once included, dominated in committees. Some beneficiaries believed ‘the programme was coming to fight against the traditional culture.’26 None of the included texts suggested that religion was addressed in the Tostan programme, although it was a chief factor in its continuance in all communities. In Senegal, one religious leader expressed strong support for FGM/C, which might have influenced the faithful.…”
Section: Resultsmentioning
confidence: 99%
“…The Village Empowerment Programme in Senegal, for example, is being implemented in 90 villages and many communities have links through marital and other social relationships to villages that are not in close proximity; consequently, the intervention appears to be having impact beyond the study sites themselves. It has proved essential to have researchers resident in the villages who use ethnographic methods to understand these social networks and communication patterns so as to map and document these 'ripple' effects (Diop et al 2004).…”
Section: Interventions Against Female Genital Cutting 473mentioning
confidence: 99%
“…In ongoing studies to evaluate the Village Empowerment Programme in Senegal and Burkina Faso, the key outcome variable is the proportion of young girls being cut who are currently not cut (Diop et al 2004); the indicator used is the proportion of daughter(s) aged 0-10 years whose mother reports that they are cut (in these countries, 95% of girls are cut by age 10 years). These studies, by necessity, followed panels of women who were exposed and not exposed to the intervention over time, and the change over time evaluated is between the two groups and not within each group.…”
Section: Indicators Of Change In Practicementioning
confidence: 99%
“…Where this has happened, it has resulted from a process of social change in which a significant number of families within a community make a collective, coordinated choice to abandon the practice so that no single girl or family is disadvantaged by the decision [26]. Often this has been done through educational activities geared to empowerment undertaken by community-based organizations, in which information about health, hygiene, nutrition, and women's rights more broadly leads to discussion of FGM and what should and can be done about it [27]. Experience has shown that only if the decision is widespread within the practicing community will it be sustained and thus bring about a new social norm that does not harm girls or violate their rights.…”
Section: Obligations and Actions To Eliminate Harmful Practices Againmentioning
confidence: 99%